PERAN SUB BAGIAN PROTOKOL DALAM PENYUSUNAN AGENDA KERJA PIMPINAN PADA BAGIAN PROKOMPIM SEKRETARIAT DAERAH KABUPATEN SIKKA - Maria Oktaviana Bengan Laba; Intan Mustafa; Viktor Ariestyan Sedu; Lodowik Nikodemus Kedoh (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2025)
This research aims to explore the role of the protocol sub-section in preparing the leadership work agenda in the Protocol and Leadership Communication Section (Prokompim) of the Sikka Regency Regional Secretariat. The Protocol Sub-Section has important responsibilities in preparing materials and compiling leadership work agendas, which contribute to the efficiency and effectiveness of implementing government tasks. Through qualitative methods, data was collected through in-depth interviews and direct observation of the work agenda preparation process. The research results show that the Protocol Sub-Section not only functions as an agenda preparer, but also as a liaison between the leadership and various related personnel, as well as as a communications manager that supports smooth operations. It is hoped that this research will provide deeper insight into the importance of the role of the protocol sub-section in improving the performance and effectiveness of government organizations in Sikka Regency.